Crustaceans associated with Cnidaria, Bivalvia, Echinoidea and Pisces at São Tomé and Príncipe islands - Wirtz, Peter (2009)
Symbiotic crustaceans were searched for at sea anemones (Actiniaria), encrusting anemones (Zoantharia), horny coral (Gorgonaria), black coral (Antipatharia), bivalves (Bivalvia), and sea urchins (Echinoidea) at São Tomé and Príncipe Islands (Gulf of Guinea, eastern central Atlantic). Sixteen species of crustaceans were found in association with these invertebrate hosts; eleven of them were new records for the area and two species, belonging to the genera Hippolyte and Heteromysis, were new for science. The thalassinid Axiopsis serratifrons was occasionally associated with an undescribed species of gobiid fish.